Understanding the Impostor Phenomenon among Active Student Organization Members in Indonesian Universities - Desy Putri Andira; Annisa Arrumaisyah Daulay (MASI Mandiri Edukasi, 2025)
The impostor phenomenon describes a psychological condition in which competent individuals feel unworthy of their achievements, doubt their abilities, and fear being perceived as incompetent. This study examines the impostor phenomenon level among active members of student association organizations in the Faculty of Da'wah and Communication. This research employed a quantitative approach with purposive sampling, involving 98 students. Data were collected using the online Clance Impostor Phenomenon Scale (CIPS) questionnaire and analyzed descriptively. The findings revealed that organizationally active students experienced a moderate impostor phenomenon, with a mean score of 60.96. The most dominant aspect was perfectionism, with a mean score of 3.36 (67%), which may trigger impostor feelings in students managing dual responsibilities, academic and organizational. The pressure to appear perfect, demonstrate leadership, and consistently fulfill responsibilities can contribute to persistent feelings of inadequacy.